2022
DOI: 10.3390/ijms23126709
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Plasma-Activated Water Impact on Photo-Dependent Dormancy Mechanisms in Nicotiana tabacum Seeds

Abstract: Seeds sense temperature, nutrient levels and light conditions to inform decision making on the timing of germination. Limited light availability for photoblastic species results in irregular germination timing and losses of population germination percentage. Seed industries are therefore looking for interventions to mitigate this risk. A growing area of research is water treated with gas plasma (GPAW), in which the formed solution is a complex consisting of reactive oxygen and nitrogen species. Gas plasma tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…PAW treatment positively influenced the photo-dependent dormancy mechanisms in Nicotiana tabacum seeds [120]. It enhanced testa and endosperm rupture percentages, increased the activity of the gibberellin-3-oxidase gene, and upregulated the expansin-A4 gene, all of which contributed to improved seed germination and growth.…”
Section: Dielectric Barrier Dischargementioning
confidence: 94%
“…PAW treatment positively influenced the photo-dependent dormancy mechanisms in Nicotiana tabacum seeds [120]. It enhanced testa and endosperm rupture percentages, increased the activity of the gibberellin-3-oxidase gene, and upregulated the expansin-A4 gene, all of which contributed to improved seed germination and growth.…”
Section: Dielectric Barrier Dischargementioning
confidence: 94%
“…Several studies have reported that direct plasma irradiation of plant seeds promotes germination and growth [72][73][74]. In the physiological process of seed germination [75], regulation of the balance of phytohormones, such as abscisic acid (ABA) and gibberellin (GA), stops dormancy, seed metabolism synthesizes enzymes, and seed germination occurs during seedling processes with regard to the softening of the cell wall and expansion of the shoot and root [76][77][78][79]. The mechanical properties of seeds change during physiological germination.…”
Section: Plasma Seed Enhancement Of Germination and Growth Of Plant S...mentioning
confidence: 99%
“…This results in the ionisation of the gas and the synthesis of a myriad of ions, reactive species, and free electrons (Wright et al 2018 ; Zhou et al 2020 ). GPAW has been shown to affect seed germination (Bafoil et al 2018 ) and to break seed dormancy (Grainge et al 2022a , b ).…”
Section: Introductionmentioning
confidence: 99%